2020
DOI: 10.1590/1678-7757-2019-0105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of calcium aluminate cement with additives on dental pulp-derived cells

Abstract: Calcium aluminate cement (CAC) has been highlighted as a promising alternative for endodontic use aiming at periapical tissue repair. However, its effects on dental pulp cells have been poorly explored. Objective: This study assessed the impact of calcium chloride (CaCl2) and bismuth oxide (Bi2O3) or zinc oxide (ZnO) additives on odontoblast cell response to CAC. Methodology: MDPC-23 cells were exposed for up to 14 d: 1) CAC with 2.8% CaCl2 and 25% ZnO (CACz); 2) CAC with 2.8% CaCl2 and 25% Bi2O3 (CACb); 3) CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Vongsavan et al locally administered 4% articaine supplemented with 1:100,000 epinephrine to the mandibular first molars and canines in healthy volunteers and used electric pulp testing methods to measure anesthetic efficacy [ 13 ]. Furthermore, Oliveira et al evaluated the anesthetic efficacy of needle-free jet injection and conventional injection needle insertion in volunteers requiring restoration of the maxillary first molars using an electric pulp testing method [ 14 ]. The findings mentioned above indicated that the electric pulp testing method could be reliable for measuring anesthetic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vongsavan et al locally administered 4% articaine supplemented with 1:100,000 epinephrine to the mandibular first molars and canines in healthy volunteers and used electric pulp testing methods to measure anesthetic efficacy [ 13 ]. Furthermore, Oliveira et al evaluated the anesthetic efficacy of needle-free jet injection and conventional injection needle insertion in volunteers requiring restoration of the maxillary first molars using an electric pulp testing method [ 14 ]. The findings mentioned above indicated that the electric pulp testing method could be reliable for measuring anesthetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements with more clinical indicators are needed to determine the clinical utility of vasopressin-supplemented lidocaine. Electric pulp testing methods are widely used as clinical perception tests for dental pulp and are widely used to assess anesthetic effects [ 11 14 ]. Therefore, this study used electric pulp testing methods to measure anesthetic effects.…”
Section: Introductionmentioning
confidence: 99%